2015
DOI: 10.1007/s10162-015-0532-x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Auditory Brainstem Responses in Prelingually Deaf and Late-Implanted Cochlear Implant Users

Abstract: Neurophysiological studies in animals and humans suggest that severe hearing loss during early development impairs the maturation of the auditory brainstem. To date, studies in humans have mainly focused on the neural activation of the auditory brainstem in children treated with a cochlear implant (CI), but little is known about the pattern of activation in adult CI users with early onset of deafness (prelingual, before the age of 2 years). In this study, we compare auditory brainstem activation in prelinguall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…Median PTA of the six NH ears was 14 dB HL (range 5 to 21 dB HL). Full insertion was achieved in all subjects with various implant types from Cochlear Ltd. Four BD subjects were prelingually deaf, defined as severe to profound binaural hearing loss with its onset before the age of 2 years (based on medical charts including diagnostic audiometry and self-reported patient information) and insufficient residual hearing during childhood for normal speech and language development ( Lammers et al 2015a , 2015 b). Duration of deafness ranged from 0.7 to 44.2 years, with a median of 7.2 years in the BD group and 1.8 years in the SSD group, which was not significantly different (Mann-Whitney U = 19, p = 0.08).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Median PTA of the six NH ears was 14 dB HL (range 5 to 21 dB HL). Full insertion was achieved in all subjects with various implant types from Cochlear Ltd. Four BD subjects were prelingually deaf, defined as severe to profound binaural hearing loss with its onset before the age of 2 years (based on medical charts including diagnostic audiometry and self-reported patient information) and insufficient residual hearing during childhood for normal speech and language development ( Lammers et al 2015a , 2015 b). Duration of deafness ranged from 0.7 to 44.2 years, with a median of 7.2 years in the BD group and 1.8 years in the SSD group, which was not significantly different (Mann-Whitney U = 19, p = 0.08).…”
Section: Methodsmentioning
confidence: 99%
“…It can be recorded in an awake and passive listening situation and it has the same typical waveform as the cortical P1-N1-P2 complex observed in response to a stimulus onset ( Kim 2015 ; Martin & Boothroyd 2000 ; Vonck et al 2019 ). The ACC mirrors auditory discrimination ( Martin et al 2008 ) and might better relate to perceptual measures ( He et al 2012 , 2014 ; Kim 2015 ; Liang et al 2018 ; Mathew et al 2017 ) than other objective measures such as electrocochleography ( Kim et al 2017 ), electrically evoked compound action potentials ( Smoorenburg et al 2002 ; van Eijl et al 2017 ), electrically evoked auditory brainstem responses ( Lammers et al 2015a ), or CAEPs in response to onset stimuli ( Barlow et al 2016 ; Brown et al 2015 ; Lammers et al 2015 b).…”
Section: Introductionmentioning
confidence: 99%
“…So far, attempts have been made to find a good model to predict speech in noise with different brainstem and cortical response paradigms, like the cortical auditory evoked potential (CAEP) and P300. However, due to a lack of clinically useful and consistent correlations, none of these objective measures have made it beyond research applications [ 23 27 ]. The prognostic ACC model is the first objective measure to predict speech in noise perception with high accuracy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Patients with prelingual deafness are particularly vulnerable to delays in CI because of a critical window for speech and language development. 20 , 21 , 22 , 23 On average, the interval between CI candidacy evaluation to CI surgery was 6 months longer for patients with prelingual deafness that were implanted during COVID‐19 compared with those implanted pre‐COVID. Numerous studies have demonstrated that timing of CI impacts speech, language, functional and social outcomes in children.…”
Section: Discussionmentioning
confidence: 99%